Physiochemical Characteristic of Sago (Metroxylon Sagu) Starch Production Wastewater Effluents - Oon, Yin Wee; Law, Puong Ling; Kopli, Bujang; Lim, Soh Fong (MG Aricent Educational Foundation, 2017)
The physiochemical characteristics of sago starch production wastewater effluents was recently studied. Sago wastewater effluent samples were obtained from a sago factory located in Sarawak, Malaysia and sent to accredited laboratories for particle size distribution and water quality analyses. The findings of this study concluded that sago wastewater effluents from this region are whitish and greyish brown (pH 4.20) in color with majority supra-colloidal or settable suspended solids of particle size ranged from 4.477 µm to 1.18 mm (of 95% volume). The starch content of this wastewater effluents are less than 7% whilst the pollutant parameters (total suspended solids, biochemical oxygen demand and chemical oxygen demand) measured 10,900 mg/L, 5,820 mg/L and 10,220 mg/L, respectively. Pre-filtration of the wastewater effluents has resulted reduction of the pollutants content as high as 66% of total suspended solids, 20% of biochemical oxygen demand and 22% of chemical oxygen demand while improved pH in a range of 0.05-0.45%.